Anaerobic Digestion of Tetracycline Spiked Livestock Manure and Poultry Litter Increased the Abundances of Antibiotic and Heavy Metal Resistance Genes - Getahun E. Agga; John Kasumba; John H. Loughrin; Eric D. Conte (Frontiers in Microbiology, 2020)
Anaerobic digestion is used for the treatment of animal manure by generating biogas. Heavy metals cause environmental pollutions and co-select for antimicrobial resistance. We evaluated the impact of mesophilic anaerobic digestion of cattle manure (CM), swine manure (SM) and poultry litter (PL) on the concentrations of seven tetracycline [tet(A), tet(B), tet(G), tet(M), tet(O), tet(Q), and tet(W)], macrolide [erm(B)], methicillin (mecA and mecC), copper (copB, pcoA, pcoD, and tcrB) and zinc (czrC) resistance genes, and three bacterial species (E. coli, Enterococcus spp. and Staphylococcus aureus). The total bacterial population and total abundance of the seven tet genes significantly increased in the three manure types after digestion. Concentration of tet(M) was strongly correlated with that of erm(B) and enterococci. As concentration of tetracyclines declined during anaerobic digestion, that of four tet genes (A, B, Q, and W) and 16S rRNA increased, that of tet(M) decreased, and that of tet(G) and tet(O) did not change. Concentrations of copB and pcoA did not change; while that of pcoD did not change in the PL, it increased in the SM and CM. While the concentration of enterococci remained unchanged in CM, it significantly increased in the PL and SM. Concentrations of tcrB significantly increased in the three manure types. While concentrations of S. aureus significantly increased in the CM and PL, that of SM was not affected. Concentrations of mecC significantly increased in all manure types after digestion; while mecA concentrations did not change in the SM, they significantly increased in CM and PL. While concentration of czrC remained low in the CM, it increased in the PL but declined in the SM. In conclusion, while mesophilic anaerobic digestion of animal manure decreased concentration of tetracyclines, it increased the concentrations of total bacteria, tet genes, E. coli, enterococci and S. aureus and methicillin resistance genes. It did not have any effect on concentrations of heavy metals; concentrations of heavy metal resistance genes either increased or remained unaffected depending on the animal species. This study showed the need for post-digestion treatments of animal manure to remove bacteria, antibiotic resistance genes, heavy metals and their resistance genes.